CFRP Conical Grid Space Structure with Embedded Fiber Optics: Design, Manufacturing and Test - Giovanni Totaro; Felice De Nicola; Paola Spena; Giovangiuseppe Giusto; Monica Ciminello; Ilan Weissberg; Yehonatan Carmi; Daniel Arviv; Nir Lalazar (Aerospace, 2023)
This article discloses the activity developed in the framework of the research project “GRID” aiming at the feasibility demonstration of a fiber optic sensing system (FOS), based on fiber Bragg gratings (FGB), embedded in the ribs of a conical grid structure demonstrator in composite material (CFRP), manufactured by means of dry robotic winding, liquid resin infusion and oven curing. This structure represents an optimized and highly efficient conical adapter for satellite applications that was designed under the same requirements of a conventional CFRP benchmark solution in order to evaluate possible mass savings. Specific interfaces were conceived in order to facilitate the insertion of the fiber optics in the center of helical ribs—pausing the automated deposition phase of the dry preform—and secure them to the structure. Representative grid articles were produced and tested to select the materials and evaluate the preliminary feasibility of the integrated system in conjunction with the infusion process. The proper functioning and use of the sensing system were finally proven during the various phases of the mechanical testing campaign of the demonstrator. Such a campaign included stiffness and strength evaluations and culminated with the catastrophic failure of the structure. The significant amount of data collected from several sensors embedded in the ribs and from conventional sensors glued outside the ribs helped us to better understand the structural behavior and to validate the design and analysis models. The main steps of the design, manufacturing and tests of this project are here addressed.